Seasonal changes in the diel vertical migration of walleye pollock (Theragra chalcogramma) in the northern Gulf of Alaska - Charles F. Adams; Robert J. Foy; John J. Kelley; Kenneth O. Coyle (Environmental Biology of Fishes, 2009)

Bottom‐up forcing and the decline of Steller sea lions ( Eumetopias jubatus ) in Alaska: assessing the ocean climate hypothesis - ANDREW W. TRITES; ARTHUR J. MILLER; HERBERT D. G. MASCHNER; MICHAEL A. ALEXANDER; STEVEN J. BOGRAD; JOHN A. CALDER; ANTONIETTA CAPOTONDI; KENNETH O. COYLE; EMANUELE DI LORENZO; BRUCE P. FINNEY; EDWARD J. GREGR; CHESTER E. GROSCH; et al. (Fisheries Oceanography, 2007)
Declines of Steller sea lion ( Eumetopias jubatus ) populations in the Aleutian Islands and Gulf of Alaska could be a consequence of physical oceanographic changes associated with the 1976–77 climate regime shift. Changes in ocean climate are hypothesized to have affected the quantity, quality, and accessibility of prey, which in turn may have affected the rates of birth and death of sea lions. Recent studies of the spatial and temporal variations in the ocean climate system of the North Pacific support this hypothesis. Ocean climate changes appear to have created adaptive opportunities for various species that are preyed upon by Steller sea lions at mid‐trophic levels. The east–west asymmetry of the oceanic response to climate forcing after 1976–77 is consistent with both the temporal aspect (populations decreased after the late 1970s) and the spatial aspect of the decline (western, but not eastern, sea lion populations decreased). These broad‐scale climate variations appear to be modulated by regionally sensitive biogeographic structures along the Aleutian Islands and Gulf of Alaska, which include a transition point from coastal to open‐ocean conditions at Samalga Pass westward along the Aleutian Islands. These transition points delineate distinct clusterings of different combinations of prey species, which are in turn correlated with differential population sizes and trajectories of Steller sea lions. Archaeological records spanning 4000 yr further indicate that sea lion populations have experienced major shifts in abundance in the past. Shifts in ocean climate are the most parsimonious underlying explanation for the broad suite of ecosystem changes that have been observed in the North Pacific Ocean in recent decades.

Hydrographic features and seabird foraging in Aleutian Passes - CAROL LADD; JAIME JAHNCKE; GEORGE L. HUNT; KENNETH O. COYLE; PHYLLIS J. STABENO (Fisheries Oceanography, 2005)
Strong tidal currents crossing over the abrupt topography of the Aleutian Passes result in regions with high horizontal property gradients. These frontal regions vary with the tidal cycle and form the boundary between vertically mixed and stratified regions. Concentrations of seabirds were associated with convergence zones in the mixed water (MW) and with the front between North Pacific (NP) water and MW. Species that were foraging by picking at prey from the surface were associated with surface convergences that appeared to be associated with Langmuir circulation cells or tidal features (all fulmar aggregations) in the central passes (Samalga, Seguam). In contrast, subsurface foraging puffins and small alcids were mostly observed in areas of turbulent, well‐mixed water near the shallow regions of the passes. Short‐tailed shearwater flocks that were plunge‐diving for prey were associated with the front between the NP water and MW in the passes. On our transects, we observed no significant aggregations of seabirds associated with Bering Sea water or NP water away from the frontal zones. The interaction of strong currents with bathymetric features results in zones of vertical advection, mixing, and surface convergences that make island passes attractive foraging regions for seabirds. Deep passes lacking these features, such as many of the passes in the western Aleutian Archipelago, are not as likely to facilitate trophic transfer to top predators as shallow passes, such as those found in the eastern Aleutian Islands.

Zooplankton distribution, abundance and biomass relative to water masses in eastern and central Aleutian Island passes - KENNETH O. COYLE (Fisheries Oceanography, 2005)
Conductivity–temperature–depth (CTD), acoustic and net samples were taken through a series of passes in the eastern and central Aleutian Island archipelago to document regional differences in the physical and biological conditions. The water column in central passes had elevated salinity and depressed temperatures, indicating upwelling of deep water through the passes. The zooplankton community included the oceanic genera Neocalanus and Eucalanus , and the euphausiid Euphausia pacifica , all oceanic taxa. Eastern passes had significantly lower salinity and elevated temperature relative to the central passes, suggesting a more neritic environment. Calanus marshallae , Pseudocalanus , Acartia and Thysanoessa inermis , common neritic species, were observed in the eastern passes. Canonical correlation indicated that up to 50% of the observed variance in mean zooplankton abundance in the passes could be explained by salinity and temperature. Elevated sound scattering was observed in fronts and eddies in the passes, particularly at the northern ends of the passes, in association with elevated zooplankton abundance and biomass. The central passes were characterized as an oceanic environment, influenced primarily by Alaskan Stream water with its associated interzonal copepod species, while the eastern passes were influenced by the Alaska Coastal Current, which contains a mixture of oceanic and neritic zooplankton species.

Tidal front affects the size of prey used by a top marine predator, the short‐tailed shearwater ( Puffinus tenuirostris ) - LUCY S. VLIETSTRA; KENNETH O. COYLE; NANCY B. KACHEL; GEORGE L. HUNT (Fisheries Oceanography, 2005)
Oceanographic features are known to influence the distribution of marine predators by affecting the abundance and distribution of their prey. We tested the hypothesis that oceanographic features also affect predator distribution by enhancing the profitability of small‐sized prey. During July and August 1999, short‐tailed shearwaters feeding in Akutan Pass, Alaska (Aleutian Islands) fed upon small (11.6 ± 0.2 mm) euphausiids present in high density near the sea surface. Conductivity–temperature–depth (CTD) casts, hydroacoustic surveys, and net tows revealed that high densities of small euphausiids were associated with a tidal front on the north side of Akutan Pass. At most sites elsewhere in the Bering Sea, away from tidal fronts, shearwaters selected larger (14.2–20.1 mm) euphausiids, even when small euphausiids were present. This study provides evidence that, by promoting high densities of easily accessible prey, oceanographic features can broaden the range of prey sizes taken by marine predators.

Annual cycle of zooplankton abundance, biomass and production on the northern Gulf of Alaska shelf, October 1997 through October 2000 - Kenneth O. Coyle; Alexei I. Pinchuk (Fisheries Oceanography, 2003)
Zooplankton abundance from March through October on the northern Gulf of Alaska shelf in 1998, 1999 and 2000 was dominated by calanoid copepods; the biomass was dominated by calanoids and cnidarians. Although we sampled during the 1997–1998 El Niño, marked interannual differences in the major copepod taxa were not observed. Zooplankton abundance and species composition were influenced primarily by mean water‐column salinity, secondarily by the mean temperature above the thermocline. An annual biomass peak, averaging about 0.5 g wet weight m −3 , occurred in May and consisted primarily of the oceanic copepod species Neocalanus cristatus, Neocalanus plumchrus and Neocalanus flemingeri . A second biomass peak, 0.5 g wet weight m −3 , was observed in August and consisted mainly of the cnidarian Aequorea spp. Copepod production, estimated from daily growth rates using temperature–body size regressions, peaked in May at about 35 mg C m −2 day −1 . Initial calculations suggest an annual copepod production on the order of 6 g C m −2 year −1 , probably less than 10% of the annual primary production. The apparent resilience of the zooplankton assemblage on the northern Gulf of Alaska shelf to the 1997–1998 ENSO may have been because of its large geographic separation from the faunal boundary between zooplankton communities in the California Current and North Pacific subarctic gyre.

Anomalous conditions in the south‐eastern Bering Sea, 1997: nutrients, phytoplankton and zooplankton - Dean A. Stockwell; Terry E. Whitledge; Stephan I. Zeeman; Kenneth O. Coyle; Jeffrey M. Napp; Richard D. Brodeur; Alexei I. Pinchuk; George L. Hunt (Fisheries Oceanography, 2001)
Anomalies in the regional weather over the south‐eastern Bering Sea during spring and summer of 1997 resulted in significant differences in nutrient availability, phytoplankton species composition, and zooplankton abundance over the continental shelf as compared with measurements in the 1980s. Calm winds and the reduction of cloud cover in spring and summer produced a very shallow mixed layer in which nitrate and silicate were depleted after an April diatom bloom. High submarine light levels allowed subsequent phytoplankton growth below the pycnocline and eventual depletion of nitrate from the water column to depths of 70 m or more. Thus, total new production during 1997 may have exceeded that of previous years when nitrate was not depleted below the pycnocline. A bloom of the coccolithophorid, Emiliania huxleyi , was observed in early July in the warm, nutrient‐depleted waters over the middle and inner shelf. Emiliania huxleyi concentrations reached 4.5 × 10 6 cells L –1 by September, and the bloom persisted through the autumn. There was evidence for increased abundance of some species of copepods in 1997 as compared with data from the middle domain in June 1981. The abundance of adult and juvenile euphausiids in 1997 was statistically similar to values measured in 1980 and 1981. However, near‐surface swarms were rarely observed on the inner shelf in August–September 1997. Lack of euphausiid availability in the upper water column may partially explain the August–September mass mortality of planktivorous short‐tailed shearwaters ( Puffinus tenuirostris ) observed on the inner shelf.